CHOROIDAL NEOVASCULARIZATION IN NORTH CAROLINA MACULAR DYSTROPHY RESPONSIVE TO ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR THERAPY. Issue Volume 15:Issues 5(2021) (September 2021) - Bakall, Benjamin; Bryan, J. Shepard; Stone, Edwin M.; Small, Kent W.
Abstract : Purpose: To report a new family with North Carolina macular dystrophy including a patient with choroidal neovascularization (CNV). Methods: Diagnostic modalities included fundus imaging, fluorescein angiography, optical coherence tomography, and genetic testing. The CNV was treated with intravitreal anti–vascular endothelial growth factor according to a treat-and-extend protocol in both eyes. Results: A 60-year-old man presented with North Carolina macular dystrophy with decreasing vision in the left eye and persistently deceased central vision in the right eye. Optical coherence tomography examination showed intraretinal and subretinal fluid consistent with CNV. Genetic testing was performed. Examination of family members showed no signs of CNV. The visual acuity improved from 20/400 to 20/150 in the right eye and from 20/100 to 20/40 in the left eye after intravitreal bevacizumab treatment for CNV. Molecular analysis of the PRDM13 gene revealed a pathogenic heterozygous point mutation. Conclusion: Recognition and treatment of CNV in North Carolina macular dystrophy can result in improved vision. Genetic testing of the PRDM13 gene can confirm a molecular diagnosis for North Carolina macular dystrophy. Abstract : A 60-year-old man with North Carolina macular dystrophy presented with a history of decreased vision and signs of choroidal neovascularization. Treatment with intravitreal bevacizumab improved the condition and visual acuity. Family members were evaluated. Genetic testing revealed a heterozygous mutation in the PRDM13 gene.